Concepções de matemáticos e egressos do IMPA sobre matemática e educação de matemática - Lorete, Eliane Oliveira (2003)
Everal studies point out the importance of investigating the teachers. conceptions, for the influence they have upon the teaching practice. In special, the conceptions a teacher has of mathematics and of mathematical education will influence his/her methodology, and the form in which he/she perceives the student s role and the teacher.s role, etc. The Association . Instituto Nacional de Matemática Pura e Aplicada. (National Institute of Pure and Applied Math) (IMPA) has stood out throughout the last five decades as an instituition of excellence in research and in researchers. education in the area of math, both nationwide and wordwide. The public universities have absorbed a great part of the egress from such institution. The Federal University of Espírito Santo is no exception, once, in June/2001, the staff in its Math Department was constituted in its majority by IMPA egress (master and/or doctorate programs). Such a fact was characterized as the main reason for the choice of those professors as subjects of this research. Such egress. master and/or doctorate program supervisors and the egress themselves were interviewed, in an attempt to find convergences and/or divergences between the supervisors (referred to as mathematicians) conceptions and the egress. conceptions about math, mathematical education, and about the IMPA, for it is believed that the education received by the IMPA egress may influence the education of the future math teachers, since such egress also teach in the Math Licentiateship. The research, of a qualitative character, was shaped as a case study, of which the data were collected by means of semi-structured interviews. The results show that among the interviewed was prevalent a conception of math very close to the Platonism, though some instrumentalist conceptions and problem solution elements were identified. Among the interviewed, a conception of traditional mathematical education stood out, though some elements of a contemporary mathematical education were perceived. As for the IMPA, both mathematicians and egress agree that the institute s recognition is due to the quality of the research carried out by them and to the exchange programs